A near‐field sea level record of East Antarctic Ice Sheet instability from 32 to 27 Myr. (25th January 2013) - Gallagher, Stephen J.; Villa, Giuliana; Drysdale, Russell N.; Wade, Bridget S.; Scher, Howie; Li, Qianyu; Wallace, Malcolm W.; Holdgate, Guy R.
Abstract : [1] Fossil, facies, and isotope analyses of an early high‐paleolatitude (55°S) section suggests a highly unstable East Antarctic Ice Sheet from 32 to 27 Myr. The waxing and waning of this ice sheet from 140% to 40% of its present volume caused sea level changes of+ 25 m (ranging from ‐30 to +50 m) related to periodic glacial (100, 000 to 200, 000 years) and shorter interglacial events. The near‐field Gippsland sea level (GSL) curve shares many similarities to the far‐field New Jersey sea level (NJSL) estimates. However, there are possible resolution errors due to biochronology, taphonomy, and paleodepth estimates and the relative lack of lowstand deposits (in NJSL) that prevent detailed correlations with GSL. Nevertheless, the lateral variations in sea level between the GSL section and NJSL record that suggest ocean siphoning and antisiphoning may have propagated synchronous yet variable sea levels. Key Points: We present an high latitude near field record of Oligocene sea level variability We show that the first EAIS was very unstable with sea level changes ‐30 to +50m Siphoning & anti‐siphoning caused different sea level in New Jersey & Australia